Krik? krak! y breath, eyes, memory de Edwidge Danticat e Insubmissas lágrimas de mulheres y Ponciá Vicencio de Conceicao Evaristo: autoficción y escrivivencia (2020)
From geographically distant places in Latin America and facing different social conditions, black women writers in this region constantly inquire in their works what it means to be a woman writer, what stories of black women are vindicated through writing and what is their role as mediators between the experience and the fictionalization. This is evidenced in works by writers such as Edwidge Danticat and Conceicao Evaristo, who despite writing from different territories of the diaspora and, therefore, being challenged by different problems, pose as poetic to construct a literary voice that accounts for the experiences of life of women in their context, their history and breaks with the limitations imposed, from the patriarchal and whitewashed interest of canonical literature, as women writers.